الملكية الخاصة للصحف في الجزائر في ظل قانون الإعلام 12-05: دراسة مقارنة مع بعض التشريعات العربية - خضير، رشيد Khudair, Rashid (جامعة الشهيد حمه لخضر الوادي, 2018)
This study examines the private ownership of the print media in Algeria. and compare them with some Arab legislation, presenting the historical course of the freedom of media ownership in different Algerian constitutions from 1963 to 2016, as well as the medias laws 1982,1990, 2012. The study focuses on the conditions were approved by the Algerian legislator in the law n° 12-05 relating to the information, which concerns the persons having the right of ownership, moral and physical, the nationality, the financial guarantee and the condition of residence of the editor. The study also examines the right of political parties and associations to own newspapers.
تتناول هذه الدراسة الملكية الخاصة لوسائل الإعلام المكتوبة (الصحف) في الجزائر ومقارنتها ببعض التشريعات العربية، وذلك من خلال التعرض إلى تطور حرية ملكية وسائل الإعلام وفقاً للدساتير المختلفة التي عرفتها الجزائر منذ 1963 إلى غاية 2016، وكذلك بالنسبة لقوانين الإعلام 1982، 1990، 2012 وتركز الدراسة على الشروط التي وضعها المشرع الجزائري في قانون الإعلام 12-05، سواء ما تعلق بطبيعة الأشخاص الذين لهم حق الملكية؛ معنويون أم طبيعيون، وجنسياتهم، الضمان المالي، وشرط الإقامة لمدير النشرية، كما تتناول الدراسة حق الأحزاب السياسية والجمعيات في امتلاك الصحف.
Keywords: الجزائر -- وسائل الإعلام -- الصحافة العربية -- القوانين والتشريعات -- القانون المقارن